Using the Severity of Dependence Scale to screen for DSM‐5 khat use disorder. (11th March 2018) - Duresso, Samson W.; Matthews, Allison J.; Ferguson, Stuart G.; Bruno, Raimondo
Abstract: Objective: This study aimed to determine the efficacy of the Severity of Dependence Scale (SDS) as a screening tool for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ‐defined khat use disorder. Methods: Cross‐sectional, purposive sample of past‐year khat consumers aged 16 and above were recruited from khat markets and cafes from university and general community in Adama, Ethiopia. Participants self‐completed a survey comprising current substance use disorder. Results: The SDS formed a unifactorial structure, consistent with the dependence construct. Almost three quarters (73%) of the sample were identified as experiencing Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition khat use disorder. The SDS demonstrated excellent discrimination (area under the curve = 0.92) and an optimal cut‐off as a score of 3 or greater, with sensitivity of 81% and specificity of 96%. This classification validly identified a group with more frequent and higher dose khat use than participants that did not screen positive. Conclusion: Although khat is a mild stimulant, there is clear evidence that some consumers are both concerned with their use and experience problems associated with their use. Consistent with its application for other drugs, the SDS is a brief and simple screening tool that appears to validly identify individuals experiencing a khat use disorder syndrome and experiencing high rates of adverse consequences in association with use.